2020
DOI: 10.3389/ffgc.2020.550884
|View full text |Cite
|
Sign up to set email alerts
|

The Cumulative Amount of Exuded Citrate Controls Its Efficiency to Mobilize Soil Phosphorus

Abstract: Root exudation of citrate is discussed as mechanism to mobilize P from the soils' solid phase. Microbial processes can mitigate the mobilization efficiency of citrate. Due to higher microbial activity in topsoils compared to subsoils, we hypothesized a lower mobilization efficiency of exuded citrate in topsoils than in the subsoils. As a model system we used microdialysis (MD) probes and we followed diffusive fluxes of citrate from the perfusate into the soil and of phosphate from the soil into the dialysate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…This finding suggests that the mineralized organic P was either absorbed by the plants, retrograded in the soil, or immobilized by microorganisms [42]. The soil's biological activity may positively influence the mobilization (accessibility) of organic P forms [43,44] or negatively hamper the P mobilization efficiency of carboxylates by way of microbial degradation [13] and biochemical factors, such as the hydrolysis rates of extracellular phosphatase enzymes [11,43,45], which play a role in plant P acquisition [46]. Other physical factors, such as variations in the soil moisture, drying conditions, and aggregate stability, may have facilitated the mineralization of organic P [46].…”
Section: Effects Of Species and Soil Types: Variations In Soil's Pbra...mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding suggests that the mineralized organic P was either absorbed by the plants, retrograded in the soil, or immobilized by microorganisms [42]. The soil's biological activity may positively influence the mobilization (accessibility) of organic P forms [43,44] or negatively hamper the P mobilization efficiency of carboxylates by way of microbial degradation [13] and biochemical factors, such as the hydrolysis rates of extracellular phosphatase enzymes [11,43,45], which play a role in plant P acquisition [46]. Other physical factors, such as variations in the soil moisture, drying conditions, and aggregate stability, may have facilitated the mineralization of organic P [46].…”
Section: Effects Of Species and Soil Types: Variations In Soil's Pbra...mentioning
confidence: 99%
“…Although the majority of residual P is scarcely assimilable by plants, certain species may be able to make this P available [9,10]. The lupine genus may be able to mobilize residual P through root exudates, releasing phosphatases [11], acidifying [12], and chelating compounds or carboxylates [13][14][15], which can enhance their growth and possibly that of subsequent crops [16,17]. However, this genus has not yet been incorporated into crop rotations in Uruguay, which typically favor winter cereal crops like wheat or barley and summer crops such as soybean or maize.…”
Section: Introductionmentioning
confidence: 99%
“…The LMWOAs content in the root system is higher than that in the litter and soil. Organic acids secreted by roots promote the absorption of nutrients (N, P, Fe, and Ca) [ 10 , 11 , 12 ]. In addition, a few studies have found that many types of LMWOAs are produced during the decomposition and leaching of forest litter [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%